Severity assessment using three common behavioral or locomotor tests after laparotomy in rats: a pilot study. (December 2020) - Zieglowski, Leonie; Kümmecke, Anna; Ernst, Lisa; Schulz, Mareike; Talbot, Steven R; Palme, Rupert; Czaplik, Michael; Tolba, René H
The aim of this pilot study was to evaluate whether behavioral or locomotor tests (Open Field (OF), rotarod (RR), and CatWalk (CW)) can help assess the severity of laparotomy in rats. The new EU Directive (2010/63/EU) mandates severity assessment in experiments involving animals. However, validated and objective methods are needed to relate trial-specific monitoring results to the degree of distress caused to individual animals. Therefore, we focused on non-invasive or minimally invasive, simple, and convenient severity assessment methods in a surgical model. To evaluate surgical severity in this model, we compared moving velocity among three commonly used behavioral test methods (OF, RR, and CW) after midline laparotomy within postoperative 7 days. In this study, 30 adult male Wistar Han rats ( n  = 10 per test) were trained in their assigned test method and subsequently subjected to surgery. Severity scoring was performed daily using a modified score sheet developed previously. In addition, blood and fecal samples were collected to analyze surgical and postoperative corticosterone metabolite levels. We found significant differences among the experimental groups in terms of the analyzed parameters. In this context, the OF test was found to be the most suitable method for severity assessment after laparotomy in rats.